Potensi, Implikasi dan Penyelesaian Sengketa Kewenangan Komisi Nasional Hak Asasi Manusia dengan Kepolisian Republik Indonesia - Wicaksono, Demas Brian (Fakultas Hukum Universitas Islam Malang, 2025)
The National Human Rights Commission and the Indonesian National Police have the same authority as investigators. In this case, of course, there must be a clear division of powers, considering that the position of the National Human Rights Commission is fragile to exercise its authority because it has yet to be regulated in the 1945 Constitution of the Republic of Indonesia. This research aims to discover the potential, implications and ways of resolving authority disputes at the National Human Rights Commission and the Indonesian National Police. This research is normative juridical research, using statutory, conceptual and theory approaches. The potential and implications of authority disputes can occur because it is not expressly regulated regarding the authority to investigate between the National Commission on Human Rights and the Indonesian National Police, and the settlement effort has not been established as a formal mechanism with a legal basis.